2022
DOI: 10.1093/jacamr/dlac132
|View full text |Cite|
|
Sign up to set email alerts
|

Real-life temocillin use in Greater Paris area, effectiveness and risk factors for failure in infections caused by ESBL-producing Enterobacterales: a multicentre retrospective study

Abstract: Background Temocillin is a β-lactam that is not hydrolysed by ESBLs Objectives To describe the real-life use of temocillin, to assess its effectiveness in infections caused by ESBL-producing Enterobacterales, and to identify risk factors for treatment failure. Methods Retrospective multicentric study in eight tertiary care hospitals in the Greater Paris area,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…12 The drug can be used for the documented treatment of complicated urinary tract infections (UTIs), pulmonary infections, bacteraemia and cutaneous infections, but it is mainly used for the treatment of UTIs. 13 , 14 In Belgium temocillin is also recommended for the empirical treatment of complicated UTIs. 15 Empirical treatment for UTIs is recommended according to the antibiotic resistance risk level adapted for the clinical criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The drug can be used for the documented treatment of complicated urinary tract infections (UTIs), pulmonary infections, bacteraemia and cutaneous infections, but it is mainly used for the treatment of UTIs. 13 , 14 In Belgium temocillin is also recommended for the empirical treatment of complicated UTIs. 15 Empirical treatment for UTIs is recommended according to the antibiotic resistance risk level adapted for the clinical criteria.…”
Section: Discussionmentioning
confidence: 99%
“… 4 There are no differences in the clinical outcome of patients treated with temocillin for infections due to E. coli , K. pneumoniae and P. mirabilis , compared with those involving E. cloacae complex or other cephalosporinase-producing strains. 13 , 18 , 19 Nevertheless, a few isolates of cephalosporinase-producing species were included in these studies. It would seem advisable to conduct further studies on infections other than those of the urinary tract, distinguishing the species of Enterobacterales and adapting the dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Salmonella strains isolated from several countries (China, Thailand, the Republic of Bulgari, and Denmark) carry extended-spectrum β-lactamases (ESBLs), which have attracted much attention around the world [ 26 , 27 , 28 , 29 ]. ESBL strains complicate antibiotic therapy [ 30 ] as ESBL-encoding plasmids can carry additional β-lactamase genes and other antibiotic resistance genes, which may limit treatment options for ESBL-producing pathogens [ 31 ]. Both the US Centers for Disease Control and Prevention (CDC) [ 32 ] and the WHO [ 33 ] list Gram-negative bacteria that produce beta-lactamases as one of the world’s most pressing threats.…”
Section: Introductionmentioning
confidence: 99%